Karl Barth and Public Theologies! Why Black Theology of Liberation is Still Relevant in the Wake of a Public Theology Euphoria? - Tshaka, Rothney (Revista Pistis & Praxis, 2022)
Karl Barth, who is considered one of the foremost reformed theologians of our time, had disabused his followers of any idea of the essence of the political in theological reflections when he insisted on the wholly otherness of God with his revised Romans commentary. Those whose interest in Barth came as a result of his activities during his stint as pastor of Safenwil, would continue to read politics into his theological metamorphosis. Thus, whether his theology falls within the realm of the relatively new hermeneutic called public theology is expected to be questioned. However, it is imperative to note that the notion of "public" is dynamic and has transformed over the ages. While there are varied public theologies, Black Theology of Liberation continues to assert its relevance in the face of the more popular public theology of South Africa.